Innovative Approaches to Enhancing Intelligent and Emotional Quotient Through Multi-Modal Neurotechnological Interventions (QEEG, TCCD, BAWE, HBOT, Board Game and Brain-Computer Interface) - Juswanto, Gerard; Mayza, Adre; Caroline, Maria; Gracia, Anne; Koesoema, AP (Eduvest - Journal of Universal Studies, 2025)
In the digital age, Generation Z and Alpha face rising cognitive-emotional challenges, including attention deficits and emotional dysregulation, necessitating innovative neurotechnological interventions. This study evaluates the efficacy of multi-modal neuroengineering—combining qEEG, BAWE, board games, and TCCD—to enhance IQ and EQ in hyperactive children. A double-blind randomized controlled trial was conducted with 6 participants (aged 9) assigned to board games, BAWE+board games, or control groups. qEEG and TCCD monitored neurophysiological changes, while cognitive and emotional outcomes were assessed via standardized tests. The BAWE+board game group showed significant IQ and EQ improvements (r = 0.72, p < 0.001), outperforming standalone interventions. qEEG revealed enhanced alpha/beta waves, correlating with cognitive-emotional gains, while TCCD confirmed optimized cerebral blood flow. This research validates integrated neurotechnologies as a scalable solution for EIQ enhancement in digital-native populations, advocating for certified, multidisciplinary implementation in educational and therapeutic settings.